Non-falciparum malaria infections in pregnant women in West Africa. (December 2016) - Williams, John; Njie, Fanta; Cairns, Matthew; Bojang, Kalifa; Coulibaly, Sheick; Kayentao, Kassoum; Abubakar, Ismaela; Akor, Francis; Mohammed, Khalifa; Bationo, Richard; Dabira, Edgar; Soulama, Alamissa; et al.
Abstract Background Non-Plasmodium falciparum malaria infections are found in many parts of sub-Saharan Africa but little is known about their importance in pregnancy. Methods Blood samples were collected at first antenatal clinic attendance from 2526 women enrolled in a trial of intermittent screening and treatment of malaria in pregnancy (ISTp) versus intermittent preventive treatment (IPTp) conducted in Burkina Faso, The Gambia, Ghana and Mali. DNA was extracted from blood spots and tested forP. falciparum, Plasmodium vivax, Plasmodium malariae andPlasmodium ovale using a nested PCR test. Risk factors for a non-falciparum malaria infection were investigated and the influence of these infections on the outcome of pregnancy was determined. Results P. falciparum infection was detected frequently (overall prevalence by PCR: 38.8 %, [95 % CI 37.0, 40.8]), with a prevalence ranging from 10.8 % in The Gambia to 56.1 % in Ghana. Non-falciparum malaria infections were found only rarely (overall prevalence 1.39 % [95 % CI 1.00, 1.92]), ranging from 0.17 % in the Gambia to 3.81 % in Mali. Ten non-falciparum mono-infections and 25 mixed falciparum and non-falciparum infections were found.P. malariae was the most frequent non-falciparum infection identified;P. vivax was detected only in Mali. Only four of the non-falciparum mono-infections were detected by microscopy or rapid diagnostic test. Recruitment during the late rainy season and low socio-economic status were associated with an increased risk of non-falciparum malaria as well as falciparum malaria. The outcome of pregnancy did not differ between women with a non-falciparum malaria infection and those who were not infected with malaria at first ANC attendance. Conclusions Non-falciparum infections were infrequent in the populations studied, rarely detected when present as a mono-infection and unlikely to have had an important impact on the outcome of pregnancy in the communities studied due to the small number of women infected with non-falciparum parasites.